Analysis of Lodging and Competition on the Island of Bali during Covid-19 with Big Data - Moch Sambas; Shanti Pujilestari; Listijono Setyopratignjo; Rina Kurniawati (The Postgraduate School of Tourism Sahid Polytechnic, 2022)
Purpose: This study aims to count the number of lodgings, map lodging density and its supporting facilities, and rank the county, as well as the lodgings available on the island of Bali during covid-19. Research methods: This study uses data related to lodging and its supporting facilities such as tourist attractions, gas stations, malls, and marts. The data were collected using the web scrapping method utilizing big data sourced from hotel.com and booking.com. The data were collected during the Covid-19 period is from August to September 2021. Spatial analysis is employed using Geographic Information Systems. Also, it uses the scoring of lodgings, their supporting facilities, and consumer reviews. Results and Discussions: The results showed that the number of lodgings on Bali Island during the Covid-19 period was 5,389 properties in a high-density area in South Bali. By taking into account the tourist supporting facilities of Badung, it has the highest level of competition. Implication: The property with high competition is the Sol House Bali Legian hotel by Melia Hotels International. Keywords: Big data, Covid-19, lodging, dispersion, competition.